Confrontation: Those Who Qualify and Those Who Do Not - Berenson, Bernard G. (Canadian Journal of Counselling and Psychotherapy, 2012)
Confrontation is an abused technique sometimes used irresponsibly and never sufficient in itself. The only people who are qualified to confront are those who demonstrate high levels of understanding which go beyond what is being said, who demonstrate deep and appropriately changing levels of regard and affect, who possess a high level of physical energy, and who possess a large and growing repertoire of helping skills.